Traditional Ulama', Islamic Traditions, and Ngaji Pasanan within the Networked Society - Mohamad Sobirin (IBDA` : Jurnal Kajian Islam dan Budaya, 2021)
In Ramadan, kiai in various pondok pesantren (Indonesian Islamic Boarding Schools) conduct lecturing activities known as "Ngaji Pasanan". This tradition has been going on for a long time ago till today. However, since 2017 up to now, it has been seen to be held by taking advantage of digital information technology through live streaming via Facebook, YouTube or other media platforms. In 2020, online â€œNgaji Pasananâ€ has become a trend nationwide. This study aims to reveal the context of the online â€œNgaji Pasanan phenomenon, which is carried out by the ulama' in pondok pesantren, by taking two samples, namely K.H. Mustofa Bisri and K.H. Said Aqil Siradj. Data collection and analysis used a netnographic approach. This study found that: First, Ngaji Pasanan of the two traditional Ulama' who used digital media were actually conducted offline, but were mediated by the internet and broadcast online. Second, through the online â€œNgaji Pasananâ€, the two traditional Ulama' not only convey the teachings in the kitab kuning but also contextualize them into socio-religious issues within the digital world, beside they also produce religious discourses and actual nationalities that are being debated by the public, whether in the online or offline context. Third, the presence of traditional Ulama' in the digital space, on the other hand, has been used by netizens to support their opinions by framing their positions on controversial religious and political issues. Fourth, the presence of traditional ulama' in the digital space is more driven by their insistence on addressing the flow of religious and national discourse in the digital space compared to their affirmation of the use of digital technology to carry out the academic tradition of pondok pesantren in Ramadan, namely "Ngaji Pasanan".